Estudio del perfil de los visitantes, en los museos del centro histórico de Loja - Rosales Torres, Ximena Paola (2024)
The tourist profile of a place serves to characterize a tourist destination, such characterization is often grounded in the visitors socioeconomic and demographic variables. This profile elucidates the tastes, preferences, expectations and needs of tourists thereby, thus enhancing the management of tourism enterprises and destinations such as the museums located in the City of Loja. Consequently, the main objective of this paper is to delineate the profile of tourists frequenting the museums in the historic downtown of Loja. The specific objectives include: to assess the offerings of these museums, and to identify the various visitor segments within them. To achieve this, a mixed-methods research approach was employed, utilizing the CESTUR methodology with a quantitative scope. The descriptive method facilitated the collection, interpretation and presentation of data derived from surveys conducted with the GEOVIT tool. Initial observations reveal that the Salvador Zaragocín Tapia Museum attracts primarily elderly visitors, as well as individuals with an affinity for the antiquity of music, particularly those engaged in music studies. Conversely, the Museum of Religious Art Madres Concepcionistas de Loja predominantly draws young adults aged 25 to 33, who seek to explore the rich narratives encapsulated in the artworks displayed within the museum. Furthermore, the Museum of Cultura Lojana, which chronicles the history of our city, primarily attracts students from various educational institutions, enabling them to gain insights into the historical journey and evolution of Loja. In conclusion, it is evident that the museums of Religious Art, the Madres Concepcionistas de Loja and the Salvador Zaragocí Music Museum, host a diverse array of local national and international visitors all of whom are captivated by the compelling stories interwoven into the historical tapestry of our city.